UPAYA MIMINIMASI WASTE PADA LINI PROSES PRODUKSI KERTAS MEMO PUTAR MENGGUNAKAN VALUE STREAM MAPPING (VSM) - I Gede Marendra (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
The manufacturing industry has an important role in improving the economy of Indonesia. PT. Indah Kiat Pulp & Paper Tbk. is one of the manufacturing industry that wants to increase its efforts to make improvements in the production process scrap products with the aim to decrease lead time and minimize waste production with lean manufacturing methods. Lead time is happening right now on average for 20.6 days which exceed management's target of 14 days. This research was conducted in order lead time and waste that occur can be known so that it can be anticipated, and can increase profitability and maintain customer satisfaction memo for PT. Indah Kiat Pulp & Paper Tbk. Lean manufacturing methods used in this study with value stream mapping tool on scrap products. Value stream mapping is done by describing the current stream mapping, identification and repair of waste, then describe the future stream mapping to then simulation output calculation of the amount of production leadtime latest results. The results showed that the lead time is reduced scrap production process 10.49 days and waste that occurs can be minimized so that the yield of production output within 20 working days at 438 rim. The implication level of customer satisfaction will increase because the product ordered is not delayed and the target company also achieved.